Investigation on the Stationary Response of Gear Time-varying System Under Stochastic Excitation - Junwei Shen; Heng Cheng (Jixie chuandong, 2021)
The study on stationary dynamic response of a gear transmission system with time-varying mesh stiffness subjected to stationary stochastic external excitation is carried out. A spur gear pair model with periodical time-varying mesh stiffness is built to include stochastic external force excitations. In order to compute the stationary response of gear system， a very efficient method， called the iterative spectral method is used. This method is derived in the frequency domain and provides the explicit power spectral density（PSD） of the response. The PSD response is expressed as a function of the bispectrum which is the bilinear Fourier transform of the bitemporal impulse response of the parametric system.